Prognostic assessment of hypoxia and metabolic markers in cervical cancer using automated digital image analysis of immunohistochemistry - Kim, Bo Wook; Cho, Hanbyoul; Chung, Joon-Yong; Conway, Catherine; Ylaya, Kris; Kim, Jae-Hoon; Hewitt, Stephen M (Journal of translational medicine, 2013)
Background Hypoxia inducible factor-1 alpha (HIF-1α), induced by tumor hypoxia, regulates tumor cell metabolism and metastasis by up-regulation of c-Met, carbonic anhydrase 9 (CA9) and glucose transporter 1 (GLUT1). The prognostic significance of hypoxia and metabolic markers is not clearly defined in cervical cancer. Here, we have examined the primary players in the hypoxia signaling pathway, by immunohistochemistry, but confirming their interactions, as well as defining which proteins are associated with outcome. Methods The study subjects were comprised of cervical intraepithelial neoplasia (CIN, n = 209), carcinoma in situ (CIS, n = 74), cervical cancer ( n = 179), and matched nonadjacent normal tissues ( n = 357). Immunohistochemistry (IHC) was performed to identify HIF-1α, c-Met, CA9, and GLUT1. IHC scoring was performed using automated digital image analysis and the association of hypoxic markers with prognostic outcome was evaluated. Results HIF-1α, c-Met, CA9 and GLUT1 expression were higher in cervical cancer than in CIN and normal cervix (all P < 0.001). Among these markers, expression of HIF-1α and c-Met were significantly different in FIGO stage ( P < 0.001 and P = 0.019, respectively) and patients with lymph node metastasis ( P < 0.001 and P = 0.010, respectively). HIF-1α expression was correlated with c-Met expression in cervical cancer ( P < 0.001). High expression of HIF-1α and c-Met showed worse 5-year overall survival rate ( P = 0.047 and P = 0.005, respectively) than low expression group, but CA9 and GLUT1 did not show significant survival difference. After adjusting the prognostic covariates, c-Met was found to be an independent risk factor (HR=3.27; 95% CI, 1.05-10.23, P = 0.041) for overall survival in cervical cancer. Conclusions We demonstrate that c-Met correlates with HIF-1α and is a poor prognostic factor in survival in cervical cancer.